Concept of Military Asset Management System in Indonesian Armed Forces (Defense and Security Studies, 2022)
The Internet of Things (IoT) is a very fast-growing technology and has a huge impact on our daily life, including military performance. In the military, IoT known as the Internet of Military Things (IoMT) or Internet of Battlefield Things (IoBT) has the function create network communication to increase readiness in the military and can apply to all aspects of military asset management and uses the interconnection, real-time, and intelligent innovation of the IoT technology to build a military asset management system. The research purpose is to analyze the Military Asset Management System (MAMs) in Indonesian National Armed Forces. The research applies a qualitative research methodology. The literature review method and the interviews were used to obtain data and analyze to describe or explain the phenomenon of problems with the Maintenance, Repair, and Overhaul (MRO) and Military Asset Management system (MAMs) in supporting the operation of the Alutsista Indonesian National Armed Forces. The research result shows that the integration of asset management in the Indonesian National Armed Forces is still not centralized, which it means needs more time to collect material asset data and of course, will impact the readiness of the military. In this case, Complex Aerial Mission Simulation (CAMS) can be a reference for Indonesian National Armed Forces to develop a Military Asset Management System (MAMs).